Tarian Bonet: Kekayaan Budaya Suku Meto di Timor yang Terlupakan (Tinjauan Filsafat Nilai Max Scheler) - Oktovianus Robertus Baunsele; Donatus Sermada Kelen (Universitas Sebelas Maret, 2024)
This paper focuses on Max Scheler's value philosophy of the Bonet traditional dance originating from the Meto tribe in West Timor, East Nusa Tenggara. Bonet dance is a traditional dance full of meaning as a place to express praise and gratitude to the Almighty for the blessings and protection that the Meto people always receive in their lives. This traditional dance that is rich in meaning and philosophical value is gradually difficult to find again, because of the existence of modern Western dances such as Dancing and Dugem which are very popular and more desirable in Timor. The purpose of this paper is to find the values that exist in this dance from the point of view of Max Scheler's philosophy of value. In this writing, the author uses the library research method to support the validity of this scientific work. The values of Bonet dance in Max Scheler's perspective are divided into four parts, namely: The value of pleasure is the lowest level that has to do with the function of sensory feelings, which includes the satisfaction and happiness of the Meto people in performing Bonet dance; The value of vitality in this dance is the creation of harmony in the group of Meto people; The value of spirituality which consists of a combination of all components of music, dance movements, and costumes as a form of total self-giving to God; The value of sanctity is the value with the highest position in the form of an expression of deep gratitude to the Creator expressed by the Creator.